Wearable Glove Based Approach for Human-UAV Interaction - Muezzinoglu, Taha; Karakose, Mehmet (Ieee, 2020)
With the developing technology in recent years, studies towards increasing UAV (Unmanned Aerial Vehicles) usage and meeting the needs in every field are rapidly increasing. Research and development studies on UAV are increasing and Human- UAV interaction is an important factor in terms of being used in many new areas. In this study, wearable smart gloves are designed for human-UAV interaction. Hand motion recognition system is created by using cheap circuit elements such as Flex sensors, imu sensor and Arduino uno in glove design. Thanks to the developed application framework, it has made it easier to determine which axis- oriented movement of the values that will correspond to the movements and to detect the signals against the movements. Standard deviation is applied to the read signal values for motion detection. When the studies conducted in the literature are examined, the biggest plus of our study is that this application, which we realize in real time, provides rapid return thanks to our simple mathematical calculation method. These motion signals obtained are used under the control of the unmanned aerial vehicle we designed in the Unity program. The data obtained from the sensors and the motion data obtained as a result of calculations with the framework we developed were sent directly to the UAV simulation and the correct controller was provided.
6th IEEE International Symposium on Systems Engineering (IEEE ISSE) -- OCT 12-NOV 12, 2020 -- ELECTR NETWORK
Keywords: Human-UAV interaction; Wearable technologies; Human-Computer interaction